Proceedings of the EACL 2014 Workshop on Humans and Computer-Assisted Translation 2014
DOI: 10.3115/v1/w14-0301
|View full text |Cite
|
Sign up to set email alerts
|

Word Confidence Estimation for SMT N-best List Re-ranking

Abstract: This paper proposes to use Word Confidence Estimation (WCE) information to improve MT outputs via N-best list reranking. From the confidence label assigned for each word in the MT hypothesis, we add six scores to the baseline loglinear model in order to re-rank the N-best list. Firstly, the correlation between the WCE-based sentence-level scores and the conventional evaluation scores (BLEU, TER, TERp-A) is investigated. Then, the N-best list re-ranking is evaluated over different WCE system performance levels:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…We have shown that the quality of phrase-level confidence estimates has a direct impact of the amplitude of the improvements that can be obtained, as well as the initial quality of the rewritten hypotheses. We have used a very simple definition for confidence estimates under the form of phrase posteriors estimated from n-best lists from an initial decoder, which obtained good empirical performance, in spite of not requiring large human-annotated datasets as in other approaches (Bach et al, 2011;Luong et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that the quality of phrase-level confidence estimates has a direct impact of the amplitude of the improvements that can be obtained, as well as the initial quality of the rewritten hypotheses. We have used a very simple definition for confidence estimates under the form of phrase posteriors estimated from n-best lists from an initial decoder, which obtained good empirical performance, in spite of not requiring large human-annotated datasets as in other approaches (Bach et al, 2011;Luong et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between our approach and the reranking baseline lies in the manner in which we expand our training data, as well as in our use of high-confidence rewritings to obtain new translation hypotheses. Importantly, this work will only exploit simple confidence estimates corresponding to phrase-based posteriors, which do not require that large sets of human-annotated data be available as in other works (Bach et al, 2011;Luong et al, 2014b). The remainder of this paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For speech-to-text applications, CE may tell us if output translations are worth being corrected or if they require retranslation from scratch. Moreover, an accurate CE can also help to improve SLT itself through a second-pass N-best list re-ranking or search graph re-decoding, as it has already been done for text translation in [2] and [19], or for speech translation in [4]. Consequently, building a method which is capable of pointing out the correct parts as well as detecting the errors in a speech translated output is crucial to tackle above issues.…”
Section: Introductionmentioning
confidence: 99%